A proposed group counseling program for the college department of Assumption College of Davao - Gallant, Lorraine (Animo Repository, 1972)
v. 1. This study proposes an organized group counseling program for the college department of Assumption College of Davao. The library method of research was used in this study. Personal observations and impressions developed were utilized to attune the information and insight gained through reading to the school setting and the needs of the college students of Assumption. Group counseling was a group activity integrated in the guidance program of the school. An in-service training of school personnel would be conducted and would precede the introduction of the program to the students. The principles on which group counseling is built was described. Skills and qualities needed by group leaders were discussed. Group discussion was considered as the main technique in solving problems. Different approaches were also considered. The different steps taken to introduce the program to the students were as follows : introduction purpose group composition place, time, and frequency of the sessions procedure used and techniques of selecting topics. The formation of groups would be based on the commonality of problems and the selection of prospective members would be made after each individual has been interviewed. A description of the first meeting and the subsequent meetings was presented. To ascertain the effectiveness of the program in meeting the students' needs, an evaluation would be conducted at the end of the group counseling experience which may last approximately one semester. It was recommended that the teacher-counselor and class advisors be given special training to perform the task of counseling students in groups. The program was meant to serve as a model for the college department of Assumption and may be implemented as presented on an experimental basis. However, it may undergo modifications in the course of its implementation to better adapt the program to the local situation. v. 2. This study aims to item-analyze the Stanford Achievement Test, Primary 1 Battery, Form X, which was administered to the Saint Scholastica's grade one pupils in February, 1972.The subjects of the study were 122 grade one pupils of Saint Scholastica's in academic year 1971-1972. The main instrument used in the study was the Stanford Achievement Test. The discriminating and difficulty indices of each test item was found through the use of the Chung-Teh-Fan Table. The effectiveness of each distractor was ascertained through the option response analysis. An overall evaluation of the test items was obtained. These analyses led to the classification of the item status of the test. It was then possible to identify the items that were to be retained, discarded, or revised. In summary, it can be stated that of the 251 items, 151 items or 62 percent were classified as acceptable items. Sixty-nine items or 27 percent were to be revised before inclusion in the test and twenty-seven items or 11 percent were to be discarded. Based on the findings of the study, it was concluded that the Stanford Achievement Test seemed to be an effective instrument for the population under study. The test as a whole seemed to be easy for the Scholasticans which suggested that the objectives embodied into each content (subtest) were being met by the pupils. Other indices suggestive of the worth of the test were the high discriminating power of the test items and the satisfactoriness of the options. There was also found to be a high correlation between the IQ and the SAT, and the SAT and teacher grades' correlation of .58 showed substantial relationship between a standardized test evaluation and teacher evaluation of pupils. It was recommended that the Stanford Achievement Test be retained for grade one Scholasticans as well as for pupils seeking admission in grade two. It was further suggested that the SAT be used as supplementary to teacher grades. Similar studies of the SAT should be made with a larger population and it was recommended t v. 3. The problem revolved around Elsie, a thirteen year old freshman high school student who was referred to the writer by the school counselor because of observed anxiety. Elsie was tense because of her low performance in Character Education and the fear of the teacher in that subject. The counselor decided to use the behavioral approach of counseling to help the counselee overcome her problems. Two goals were set: 1) to help Elsie perform well in Character Education and 2) to help her overcome her fear of her teacher in that subject. To help achieve these goals, different SPAM treatments were used. These took the form of behavior contracts, which embodied specific terms, which were specific, pertinent, attainable, and measurable. Behavior contract 1 dealt with scholastic performance in Character Education, which she wanted to increase. As a means to succeed, she agreed to prepare her own notes since there was no specified textbook for the subject. Since reinforcement, a basic principle in the SPAM treatment, plays an important role in behavior modification, a reward chart was prepared on which Elsie plotted her own progress. Seeing her progress, coupled with verbal reinforcements from the counselor, was very reinforcing in her case. Meanwhile, Systematic Desensitization was used to help Elsie free herself of the tense feelings experienced in the presence of her Character Education teacher. Since the reward chart appealed much to her, it was again chosen as a reinforcer for Behavior contract 2. The terms of this contract consisted of practicing deep muscle relaxation daily and performing systematic desensitization with the counselor twice a week for the first month and once a week by herself for the second. Elsie was requested to report to the counselor twice a week for a period of one month to brief her on her progress. The reporting for the second month was to be once a week. There was smooth progress throughout the counseling process. Both Elsie and the counselor were very happy to see both goals had been